Student Finance : Learning from Global Best Practice and Financial Innovations - Abdo, Maryanna (International Finance Corporation, Washington, DC, 2016)
Demand is also fueled by other factors: in many emerging economies a ‘demographic dividend’ of young people, the product of significant reductions in child and infant mortality rates—is poised to enter education and work. And, according to the 2014 Millennium Development Goals report, nearly 90 percent of children in developing regions are on track to complete primary education. The shift from agricultural to knowledge-based economies also plays a significant role in creating demand for higher learning. The purpose of the study was to identify key success factors in private sector student lending in order to support IFC in understanding, and potentially making investments, in student lending across a range of emerging markets. The study examined 70 student lending models globally as well as a range of innovative financial models. Detailed case studies were developed for eight compelling and diverse private sector student lending models. The study also highlighted a range of innovative financial models including crowd funding, big box banking, social impact bonds, and other mechanisms. The purpose of this investigation of innovative financial models was to see what leading-edge methods might be at work in other sectors and to see if they might offer inspiration to student lending.